1992
DOI: 10.1007/bf00290259
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glycosaminoglycans in human serum after oral administration of chondroitin sulfate

Abstract: Chondroitin sulfate was administered orally to six healthy volunteers, six patients with rheumatoid arthritis and six patients with osteoarthritis. Blood was collected at intervals before and after treatment and the glycosaminoglycan concentration was analyzed in serum using a sensitive assay based on the metachromatic reaction with 1,9-dimethylmethylene blue. The glycosaminoglycan concentration in serum before and after ingestion of chondroitin sulfate was statistically unchanged in all of the subjects studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 41 publications
1
39
0
2
Order By: Relevance
“…Baici et al (1993) investigated the ability of an oral dose of CS to impact the concentration of GAGs in humans. In this study, CS samples were administered to six healthy volunteers, six patients with rheumatoid arthritis, and six patients with OA.…”
Section: Metabolic Fate Of Orally Administered Chondroitin Sulfatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Baici et al (1993) investigated the ability of an oral dose of CS to impact the concentration of GAGs in humans. In this study, CS samples were administered to six healthy volunteers, six patients with rheumatoid arthritis, and six patients with OA.…”
Section: Metabolic Fate Of Orally Administered Chondroitin Sulfatesmentioning
confidence: 99%
“…In this study, CS samples were administered to six healthy volunteers, six patients with rheumatoid arthritis, and six patients with OA. The concentration of GAGs in serum was reportedly unchanged following ingestion (Baici et al, 1993). Morrison (1977) has indicated that the intact absorption of CS was extremely low, estimating the absorption rate to be between 0 and 8%.…”
Section: Metabolic Fate Of Orally Administered Chondroitin Sulfatesmentioning
confidence: 99%
“…This would suggest that feeding CS mainly inhibits antigen-specific Th2 differentiation and only slightly affects antigen nonspecific differentiation. It is difficult to accept that orally administered CS is systemically distributed to connective tissues such as cartilage and skin and that exogenously administered CS actually directly stimulates chondrocyte synthesis of extracellular matrix components, because CS is poorly absorbed through the digestive system (24,25). Moreover, the half-life of CS in the circulatory system is only 3-15 min, based on the pharmacokinetic study of intravenously administrated CS (26).…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharides such as CS are poorly absorbed through the digestive system (24,25). Therefore, we examined the half-life of CS in the circulatory system and demonstrated it to be 3-15 min, based on the pharmacokinetic study of intravenously administrated CS (26).…”
mentioning
confidence: 99%
“…Nevertheless, a major problem in the successful clinical use of CS is its poor intestinal absorption, resulting from its high molecular weight, charge density, and hydrophilicity. 27,28) Thus, the enhancement of intestinal absorption of CS is important in its successful application.…”
mentioning
confidence: 99%